Shear-induced alignment in 3D-printed nitrile rubber-reinforced glass fiber composites. (15th January 2022) - Yang, Guiyan; Qin, Limin; Li, Mengru; Ou, Kangtai; Fang, Jiang; Fu, Qiang; Sun, Youyi
Abstract: Nitrile rubber composite with aligned glass fibers (GFs/NBR composites) were prepared by direct-ink-writing (DIW) technology for application in flexible thermal management of electronic equipment.The alignment and orientation (0°, 45° and 90°) of glass fibers was precisely tuned by shear force field and 3D printing direction. Furthermore, the effect of print direction on the mechanical properties, thermal conductivity and heat dissipation performance were investigated. The tensile strength (1.78 MPa) and thermal conductivity (1.2 W m −1 K −1 ) of GFs/NBR composites with a 90° orientation was improved to be 149.6% and 300% compared to the composites with disordered orientation, respectively. The temperature of LED device and computer' CPU covered with GFs/NBR composites with a 90° orientation was reduced by ca. 8.1 °C and 4.1 °C, respectively. The study confirmed the formation of GFs/NBR composites with controlled alignment and orientation for various applications.